Three-dimensional effects on cracked components under anti-plane loading (Fracture and Structural Integrity, 2015)
The existence of three-dimensional effects at cracks has been known for many years, butunderstanding has been limited, and for some situations still is. Understanding improved when the existence ofcorner point singularities and their implications became known. Increasingly powerful computers made itpossible to investigate three-dimensional effects numerically in detail. Despite increased understanding, threedimensionaleffects are sometimes ignored in situations where they may be important. The purpose of thepresent investigation is to study by means of accurate 3D finite element (FE) models a coupled fracture modegenerated by anti-plane loading of a straight through-the-thickness crack in linear elastic plates. An extendedversion of the present work has recently been published in the literature.The results obtained from the highly accurate finite element analyses have improved understanding of thebehaviour of through cracked components under anti-plane loading. The influence of plate bending isincreasingly important as the thickness decreases. It appears that a new field parameter, probably a singularity, isneeded to describe the stresses at the free surfaces. Discussion on whether KIII tends to zero or infinity as acorner point is approached is futile because KIII is meaningless at a corner point.The intensity of the local stress and strain state through the thickness of the cracked components has beenevaluated by using the strain energy density (SED) averaged over a control volume embracing the crack tip. TheSED has been considered as a parameter able to control fracture in some previous contributions and can easilytake into account also coupled three-dimensional effects. Calculation of the SED shows that the position of themaximum SED is independent of plate thickness. Both for thin plates and for thick ones the maximum SED isclose to the lateral surface, where the maximum intensity of the coupled mode II takes place.
Keywords: Anti-plane loading